Low sidelobe planar electrically large sparse array antenna with element number reduction based on genetic algorithm - Zhu, Yangkun; Ma, Wenyu; Wang, Chuang; Cao, Wenquan (IET microwaves, antennas & propagation, 2024)
Conventionally, both electrically larger (EL) arrays and sparse arrays offer the advantage of element number reduction but disadvantage of high sidelobe levels. A new scheme of planar EL sparse array antenna based on a genetic algorithm (GA) to achieve low sidelobe with element number reduction is proposed. To begin with, EL sparse array antenna optimisation models based on GA for both linear and planar arrays are analysed. Then, an EL slot antenna element based on a 3 × 3 substrate integrated waveguide cavity is designed. An 8‐element linear EL sparse array antenna is designed and compared with a uniform array antenna, demonstrating a reduction in the maximum sidelobe level (MSLL) by nearly 4.6 dB. After that, a 4 × 8 element planar EL sparse array antenna is fabricated and measured. Compared to an 8 × 16 element planar EL uniform array antenna, the number of antenna elements is reduced by 75%, while the MSLL is reduced by approximately 3 dB. The measured −10 dB impedance bandwidth ranges from 25.3 to 27.8 GHz. At the central frequency, the radiation pattern achieves a peak gain of 29.6 dBi, exhibiting low sidelobe levels below −15.0 dB. The authors comprehensively analysed the electrically larger (EL) property of antenna elements, mutual coupling among elements, the feed network, and the overall design of the antenna, and proposed a planar EL sparse array antenna with elements number reduction based on a genetic algorithm to solve the problems of high sidelobe level, high processing complexity, and high manufacturing cost in the overall array antenna system.